A study on mechanical strength and stability of partially-fused carbon nanotube junctions. (April 2021) - Bhusal, Shusil; Sihn, Sangwook; Varshney, Vikas; Roy, Ajit K.
Graphical abstract: Abstract: A systematic approach has been developed to generate and predict failure strengths of single-walled carbon nanotube (CNT) junctions with various sets of non-hexagonal defects (i.e., five-, seven-, eight-membered carbon rings). Each generated junction is optimized using molecular mechanics combined with molecular dynamics simulations to attain globally energy-minimized structures. The energetic stability of barely-fused junctions is compared with fully-fused cases. Furthermore, CNT junctions with different degrees of overlaps are analyzed and discussed in detail for the failure strength with maximum stresses and strains as well as their failure mechanisms.